2019
DOI: 10.46281/ijafr.v4i2.420
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Islamic Banks: The Impact of Religiosity and the Moderating Role of Trust

Abstract: The purpose of this study is to analyze the impact of Muslim religiosity on attitudes towards Islamic Banks, considering the moderating role of public trust that exists towards these Islamic financial institutions. It identifies how trust towards Islamic banks in terms of their conformity with Shari’ah principles and their safe handling of deposits would affect common attitudes towards them. Data for the study was collected through questionnaires from 113 individuals participated in the survey. The data was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Prior studies have confirmed that RL may have a direct or indirect effect on consumer purchase behaviour (Alam, Mohd, & Hisham, 2011), bank performance (Raksayudha & Suhartanto, 2019), and the intention to use Islamic finance (Zaid, 2019;Zauro, 2017). The current findings reveal an insignificant direct effect of religiosity (RL) on the perceived inclusion of Islamic finance (PIIF).…”
Section: The Influence Of Religiosity (Rl) On the Perceived Inclusive...supporting
confidence: 54%
See 4 more Smart Citations
“…Prior studies have confirmed that RL may have a direct or indirect effect on consumer purchase behaviour (Alam, Mohd, & Hisham, 2011), bank performance (Raksayudha & Suhartanto, 2019), and the intention to use Islamic finance (Zaid, 2019;Zauro, 2017). The current findings reveal an insignificant direct effect of religiosity (RL) on the perceived inclusion of Islamic finance (PIIF).…”
Section: The Influence Of Religiosity (Rl) On the Perceived Inclusive...supporting
confidence: 54%
“…This study predicts the influence of attitudes towards Islamic finance (ATTIF), financial experience (FE), religiosity (RL), and social influence (SI) on perceived inclusion of Islamic finance (PIIF). These assumptions are based on the findings of prior studies (Karlan, Osman, & Shammout, 2021;Zaid, 2019;Zauro, 2017), social learning theories, and the financial capability approach (Bandura, 1977;Kempson et al, 2013). In addition, this study proposes the mediating role of ATTIF (Ajzen, 1991;Saurabh & Nandan, 2018;Sundarasen & Rahman, 2017) and the moderating effect of Islamic financial literacy (IFL).…”
Section: Research Framework and Hypothesis Formulationmentioning
confidence: 99%
See 3 more Smart Citations